Research progress of triglyceride-glucose index with type 2 diabetes mellitus and diabetic foot ulcer - SHEN Xinyi, LIU Qingyang (Zhongguo linchuang yanjiu)
Diabetic foot ulcer is a serious complication of diabetes mellitus, usually caused by neuropathy and peripheral arterial disease. Studies have shown that insulin resistance is a known risk factor for diabetic foot ulcer. Triglyceride-glucose index (TyG index) is a good alternative biomarker to evaluate insulin resistance. A review of the research progress on TyG index with type 2 diabetes mellitus and diabetic foot ulcer is presented.